RURAL LIVELIHOOD TRANSFORMATION AS AN EFFECT OF JATIGEDE DAM DEVELOPMENT IN SUMEDANG WEST JAVA - Arni Muslimah Handayani Widjaja (Journal of Green Science and Technology, 2022)
Jatigede dam development in Sumedang, West Java, was planned in the 1960s and facing a dynamic revolution in Indonesia’s Governmental System. The political shift causes a change in the government’s priority of development, and as a result, this project had been postponed for decades. In the 1980s, The Government had given land compensation to the rural householder who lives at the site plan. The long-postponed development execution makes rural people unaware to leave the site and continue living on the compensated land for generations. Then in 2012, Government decides to execute the development as a targeted Indonesian Economic Master Plan to boost economic growth. This sudden regulation causes shock and stress for rural people’s livelihood since they should change their way of living in a short time since access to resources became limited by inundation. However, the Dam development unavoidably causes rural transformation that has an impact on rural people’s livelihood. Rural Livelihood transformation can be seen in livelihood assets including natural, financial, physical, human, and social assets condition after the inundation. This paper aims to identify the condition of rural livelihood assets as an impact of rural transformation caused by Jatigede Dam development in Sumedang, West Java. Therefore, the study outcomes were determined as a recommendation for preventing vulnerability by implementing programs for the impacted rural household.